Production of Branched Tetraether Lipids in the Lower Pearl River and Estuary: Effects of Extraction Methods and Impact on bGDGT Proxies - Zhang, Chuanlun; Wang, Jinxiang; Wei, Yuli; Zhu, Chun; Huang, Liuqin; Dong, Hailiang (Frontiers in Microbiology, 2012)
Branched glycerol dibiphytanyl glycerol tetraethers (bGDGTs) are known as bacterial lipids that occur widely in terrestrial environments, particularly in anaerobic peat bogs and soil. We examined the abundance and distribution of bGDGTs in both core (C) and polar (P) lipid fractions from the water column and surface sediments in the lower Pearl River (PR) and its estuary using two extraction methods (sonication vs. Bligh and Dyer). A number of soil samples in the lower PR drainage basin were also collected and extracted for bGDGTs using the sonication method. The results showed aquatic production of bGDGTs as supported by substantial abundances of P-bGDGTs in the water column and sediment samples. The bGDGT-based proxies (BIT, CBT, and MBT) were not affected by the method of extraction when C-bGDGTs were analyzed; in such case, the pHCBT of the sediments reflected the soil pH of the lower PR drainage basin, and the temperature close to the annual mean air temperature in the lower PR basin. On the other hand, the P-bGDGT-derived proxies were inconsistent between the two methods. The P-bGDGTs (particularly those extracted using the sonication method) may not be reliable indicators of annual mean air temperatures.